Identifying facilitators, barriers, and strategies to implement social determinants of health screening, referral, and follow-up in the US: a scoping review protocol. Issue 6 (22nd June 2022) - Gagnon, Kelly; Ortiz-Siberón, Ángel; Patel, Nirali Deepak; James, Richard; Hawk, Mary; Damian, April Joy; Beidas, Rinad
ABSTRACT: Objective: This review will assess the literature exploring facilitators, barriers, and strategies for the implementation of social determinants of health and social needs screening, referral to community resources, and follow-up in clinical settings and clinical training curricula in the United States. Introduction: Social determinants of health and social needs are a central cause of health inequity and poor health outcomes in the United States. Existing research primarily focuses on theoretical implications of social determinants of health on health outcomes, with a growing secondary focus on the development of screening tools that identify patients' specific unmet social needs. However, summative research has not yet focused on the barriers, facilitators, and strategies relating to the implementation of social determinants of health and social need screenings into routine clinical care. This scoping review aims to examine literature on the implementation of social determinants of health and social needs screening in clinical settings and clinical training curricula while also identifying gaps that require further exploration. Inclusion criteria: This review will include relevant studies examining the facilitators, barriers, and strategies for the implementation of social determinants of health and social needs screening, referral, and follow-up as they relate to human subjects. The literature must be in English from 2010 and focus on United States clinical health settings and curricula. Methods: We will search PubMed, CINAHL, and Embase databases for relevant articles. Two independent reviewers will screen abstracts for eligibility. Data will be extracted from eligible articles and results will be presented in narrative and tabular format in line with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews.